Down But Not Out: The Case of Long-period Comet C/2021 O3 (Panstarrs) - David Jewitt; Jing Li; Michael Jaeger; Yoonyoung Kim (The Astronomical Journal)
We combine ground- and space-based observations of long-period comet C/2021 O3 (Panstarrs; perihelion distance 0.287 au) in order to investigate its reported near-perihelion destruction. Preperihelion photometric observations show a remarkably small heliocentric dependence of the scattered light, $\propto {r}_{H}^{-s}$ with s  = 2.59 ± 0.21, distinct from values reported in other long-period comets, for which s = 4 is the canonical standard. The index is smaller than expected of coma production by equilibrium sublimation of either supervolatiles (for which s  ∼ 4 is expected) or water ice ( s  ∼ 6–8) across the ∼4 to 2 au range. The absolute magnitude deduced from the preperihelion data is H = 13.0 ± 0.3 (coma scattering cross section ∼225 km ^2 for an assumed geometric albedo 0.04), while after perihelion the cross section fades by a factor of 25 to H = 16.5 (∼9 km ^2 ). STEREO spacecraft observations near perihelion show a long debris trail whose properties are consistent with forward scattering from radius ∼7 μ m particles. The data show that the nucleus of C/2021 O3 was not destroyed at perihelion. Although the light curve from 3.9 au inbound to 0.8 au outbound is not uniquely determined, a simple explanation is provided by seasonal dimming on a nucleus having high obliquity and an asymmetric distribution of near-surface volatiles. The survival of the nucleus against rotational disruption suggests a preperihelion nucleus radius r _n  ≳ 1.0 km, while the photometric limit to the radius of the nucleus after perihelion is r _n  < 1.7 km (geometric albedo 0.04 assumed).